2023
DOI: 10.1002/ima.22967
|View full text |Cite
|
Sign up to set email alerts
|

Structural biomarker‐based Alzheimer's disease detection via ensemble learning techniques

Amar Shukla,
Rajeev Tiwari,
Shamik Tiwari

Abstract: Alzheimer's disease (AD) is a degenerative neurological disorder with incurable characteristics. To identify the substantial solution, we used a structural biomarker (structural magnetic resonance imaging) to see the neurostructural changes in the different regions of the brain of AD, mild cognitive impairment, and cognitive normal subjects. In this study, we detected the AD and their subtypes by using the traditional machine learning and ensemble learning models. It is also identified the relative impact scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“… Shukla et al (2024b) analyzed a subcortical structure in AD using ensemble learning approaches. The combination of MRI and PET modalities is shown in this work, which could boost result visualization.…”
Section: Related Workmentioning
confidence: 99%
“… Shukla et al (2024b) analyzed a subcortical structure in AD using ensemble learning approaches. The combination of MRI and PET modalities is shown in this work, which could boost result visualization.…”
Section: Related Workmentioning
confidence: 99%
“…Consequently, this approach created distinct datasets consisting of patch sizes ranging from 32 to 88. In [30], the authors employed a structural biomarker known as structural magnetic resonance imaging to examine the alterations in neurostructure within various brain regions among individuals with AD, mild cognitive impairment (MCI), and those with normal cognitive function. The study employed conventional machine learning and ensemble learning models to identify AD and its various subtypes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Promisingly, a growing number of brain MRI techniques can serve as a useful non-invasive biomarker to gauge region-specific neurodegenerative processes, including Alzheimer's diseaserelated early changes (Kress et al, 2023;Shukla et al, 2023;Xie et al, 2023). Recent studies suggested that a variety of brain structures (e.g., fornix, cingulum, entorhinal and parahippocampal cortices, posterior cingulate, and precuneus) may exhibit changes early in the Alzheimer's disease process (Berron et al, 2020;Echavarri et al, 2011;Lacalle-Aurioles and Iturria-Medina, 2023).…”
Section: Introduction (818 Words)mentioning
confidence: 99%